Implementation of Standard Operating Procedures 'Cold Kitchen' in Food Storage Process at Hotel Indonesia Kempinski Jakarta - Kamilianada, Alya (UI Scholars Hub, 2025)
The background of this study was conducted to find out how a kitchen must have SOP (Standard Operating Procedure), because the kitchen is very influential in supporting food management operations at Cold Kitchen Hotel Indonesia Kempinski Jakarta and to find out the system of storage procedures for perishable food ingredients has an important role as the main raw material in making types of menus in cold kitchens as a provider of various types of fruits and vegetables. The problem formulation consists of: (1) How to strive for the implementation of SOP (Standard Operating Procedures) in the process of storing foodstuffs in order to ensure smooth production in the cold kitchen? (2) What should be done when storing goods in a kitchen? (3) What is the effect of implementing SOP (Standard Operating Procedure) when storing food ingredients in cold kitchens? The objectives of this study are (1) Knowing the application of SOP (Standard Operating Procedures) in the process of storing food ingredients in order to streamline production in cold kitchens (2) Knowing how the storage process so that there is no contamination of food ingredients (3) Knowing the final results obtained by applying SOP when storing food ingredients in cold kitchens. Data collection methods used include (1) research methods, (2) observations and interviews, (3) literature studies. The SOP (Standard Operating Procedure) system in the cold kitchen of Hotel Indonesia Kempinski Jakarta is still not implemented optimally so that it still needs a responsibility for themselves and their work so that their performance is maximized.